2013
DOI: 10.1155/2013/159570
|View full text |Cite
|
Sign up to set email alerts
|

Essentials of Oncothermia

Abstract: Oncothermia is a method of hyperthermia in oncology, controlling the locally applied deep heat by selectively targeting the cellular membrane of the malignant cells. The selection of the method is based on various biophysical and biochemical achievements. There are various differences between the malignant and healthy cells, which could be used for their selection by heat targeting. The primary selection factor is a different metabolic activity which creates distinguishable environments of the malignant cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 81 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…mEHT concentrates the modulated radiofrequency current to intercellular electrolytes and generates a temperature gradient, thereby destroying the tumour cell membrane and leading to apoptosis or necrosis [9,10]. Many clinical studies have shown that mEHT is effective for controlling advanced primary and metastatic malignancies in liver cancer, bone (metastatic) cancer, breast cancer and malignant glioma [11,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mEHT concentrates the modulated radiofrequency current to intercellular electrolytes and generates a temperature gradient, thereby destroying the tumour cell membrane and leading to apoptosis or necrosis [9,10]. Many clinical studies have shown that mEHT is effective for controlling advanced primary and metastatic malignancies in liver cancer, bone (metastatic) cancer, breast cancer and malignant glioma [11,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The principle of hyperthermia is to achieve tumour temperatures in the range of 40-46 C by controlling temperature alone [7]. More recently developed mEHT is based on the principle of classical hyperthermia, except that mEHT is physically designed to give an energy dose by regulating radiofrequency (RF) power level with an electronic device, replacing the single temperature concept of hyperthermia [7][8][9][10]. mEHT promotes direct absorption of the modulated RF current into the extracellular fluid, creating a slight temperature difference (1/1000 C) between the inner and outer temperature of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Oncothermia is a capacitive impedance coupled energyabsorption, it heats the sensitive parts of the malignant cells selectively and effectively. The details of these effects were discussed in numerous papers and chapters of books [43,[46][47][48][49][50][51][52][53].…”
Section: Hyperthermia Heating Equipment and Techniquesmentioning
confidence: 99%
“…It is based on a strong synergy between the temperature and the electric field [70]. The Radiofrequency (RF) current is chosen with a proper amplitude modulated radiofrequency [71], which is absorbed by the nanoscopic range of the malignant cells (45). The physiological differences of the malignant cells from their healthy counterparts [68] distinguishes the malignancy which is self-selected by additional time-fractal modulation [72], and on such way it is also highly personalized [73].…”
Section: Hyperthermia Heating Equipment and Techniquesmentioning
confidence: 99%
“…The complex modulated signal works effectively on the selection of malignant cells and promotes the heat dispersion of the membrane-bounded water states. Together with the state-of-the art fractal physiological considerations the concept is based on Warburg's principle of fermentative ATP production and on Szent-Gyorgyi's principle of permittivity changes of malignant membranes [69]. There are numerous clinically proven advantages of oncothermia recognized [67].…”
Section: Possible Answers To the Challengesmentioning
confidence: 99%